Kontribusi Pemerintah Daerah dalam Peningkatan Efektivitas Pajak Sarang Burung Walet Di Kabupaten Rokan Hulu - Wibowo, Sakti; Dwi Fionasari; Norra Isnasia Rahayu (Politeknik Raflesia Press, 2025)
This study aims to analyze the local government's contribution to improving the effectiveness of edible bird’s nest tax collection in Rokan Hulu Regency. The tax represents a potential source of local revenue; however, its realization remains suboptimal. This research adopts a qualitative approach using descriptive methods. Data were gathered through interviews with officials from the Regional Revenue Office, edible bird’s nest business owners, and relevant documentation. The findings indicate that the local government's contribution has not been optimal, as seen in the lack of outreach, limited supervision, and ineffective tax rate determination and collection systems. Moreover, the participation of business actors is low due to limited understanding and lack of trust in the regional tax management system. The study concludes that the effectiveness of edible bird’s nest tax collection can be enhanced through policy reform, improved capacity of tax officers, and stronger collaboration between the government and business stakeholders.